Verificação de desempenho do ensaio de neutralização viral para detecção de anticorpos para o vírus da Febre Aftosa - Valdenia Lopes da Silva Gonçalves (2019)
Brazil is one of the countries with the greatest international prominence in agribusiness, due to the increase of exports in this sector of the economy. A disease of great impact for national livestock farming is Foot-and-Mouth Disease (FMD), which has great social and economic importance. FMD is a highly infectious, highly disseminated viral disease that affects split cloven-hoofed animals, causing fever, lameness, vesicular lesions on the paws, tongue, snout and teats. It is a sanitary barrier to international trade, and demands high investments for control and prevention. Footand-Mouth disease virus (FMDV) has seven serotypes, which are immunologically distinct, O, A, C, SAT-1, SAT-2, SAT-3 and Asia 1, serotypes that are not uniformly distributed throughout the world. O, A and C serotypes have the highest distribution and are responsible for outbreaks, especially in Brazil. Serological methods for diagnosis and evaluation of FMDV, such as the viral neutralization test (NV), are essential for the diagnosis of the infection and evaluation of the efficacy of the vaccines used. The objective of this work was to verify the performance of the NV method, based on the evaluation of samples of bovine sera vaccinated with the FMD vaccine produced in Brazil. The samples were collected, after 28 days of vaccination and 28 days after booster vaccination. It was possible to verify the performance of the virus neutralization method of antibodies to the foot-and-mouth disease virus satisfactorily. The results of measurement uncertainty, repeatability and reproducibility were within the expected limits of evaluation, proving the effectiveness and guaranteeing the quality of the test method. The pilot test for the evaluation of the potency of the Foot-and-Mouth disease vaccine, performed by ELISA, reached a Percent Protection Expectancy (EPP) above 99% for the three vaccine serotypes, proving the efficacy of the vaccine used. Values of r1 and EPP, evaluating the combination of viral serotypes of the vaccines and the field isolates, the results of r1 showed that the serotype C isolate had the highest antigenic similarity to the vaccine strain, and the O and A isolates had less antigenic similarity to the vaccine viral strains. The EPP results showed that the vaccine serotypes have greater antigenic similarity with the evaluated viral isolates.